Sclerotinia sclerotiorum (mofo branco): avaliação das propriedades mutagênicas in vivo - Giannini, Laila Santos Vieira (2016)
The crop of soybean, beans, canola, cotton, peas, lettuce, potatoes, currently represent one of the most important agricultural activities in Brazil. These crops have been threatened, leading to losses of up to 70% of its total volume by the presence of soil fungus called popularly white mold or rot soil, the species Sclerotinia sclerotiorum. This fungal species is characteristic to be filamentous and cause necrosis in their hosts, and often find themselves in the granules form (sclerotia) which mix themselves with the seeds in the stages of harvesting and cleaning, thereby they can reach the final consumer in batches containing up to half of its grains contaminated by dormant mycelium of the fungus For identification of suitable solvents for extraction of compounds of sclerotia chromatographic tests were performed which indicated the choice of ethyl acetate to extract production. fungal diets containing 6, 60, and 600 mg of extract in 100 g of feed were prepared, resulting in a consumption of 25, 240 and 2600 mg of extract per kg body weight. In the in vivo study, the consumption of fungal feed caused no nutritional changes in animals. The comet test showed an increase in the length of comet tail 106,34; 174.77 and 131.90%. in blood; increase of Tail Moment 166%, 380% and 271% (lymphocytes) and 660%, 639% e 429% (liver) and increase of 129%, 212% and 160% (lymphocytes) and 284%, 296% and 260% (liver) in % of DNA in tail. Micronucleus tests in bone marrow and colon showed increased micronuclei frequency 186.95%; 147.82%; 239.13% to 202.63 and erythrocytes; 173.68 and 223.68% in colon cells. This result was also significant for apoptosis test showing increased 568.88, 513.33 457,77e% in the number of apoptotic cells. These results demonstrate the mutagenic action of sclerotia of Sclerotinia sclerotiorum, which may be from the DNA breakage, as changes in spindle fiber or chromosomal rearrangements associated or not with DNA fragmentation. These aspects render the compounds sclerotia that should be subject to further study on these damaging effects, as they can reach the food intake of humans and animals through contaminated food and feed, respectively.and the other half mixed with the sclerotia.